Comparison of clinical manifestations and immunoreactivities of Meckel's diverticulum with and without gastric heteroplasia - Zhang, Ting Ting; Zhou, Xiao Gang; Cai, Peng; Zhang, Rui Yun; Zhu, Zhen Wei (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to characterize the clinicopathological features of pediatric Meckel's diverticulum (MD) and to evaluate the diagnostic performance of imaging modalities, with particular emphasis on the role of heterotopic mucosa.MethodsA retrospective analysis was conducted on 111 surgically confirmed pediatric MD cases from 2017 to 2023 at a tertiary pediatric center. Patients were stratified into heterotopic and non-heterotopic groups based on histopathological findings. Demographic, clinical, imaging, and immunohistochemical data were analyzed using SPSS version 26.0.ResultsThe cohort exhibited a male predominance (ratio 4.29:1) and early age of onset, with 28.8% of patients aged ≤3 years. Heterotopic mucosa, predominantly gastric (74.8%), showed a strong correlation with gastrointestinal bleeding (p < 0.0001), whereas non-heterotopic patients more frequently presented with obstruction. Technetium-99m pertechnetate scintigraphy demonstrated significantly higher sensitivity compared with ultrasound (p < 0.001). Immunohistochemistry revealed SOX2/MUC5AC expression in heterotopic tissue, in contrast to CDX2 dominance in non-heterotopic patients. All patients underwent successful resection, with no significant differences in outcomes based on the surgical approach employed.ConclusionsHeterotopic mucosa defines distinct MD subtypes, each with characteristic clinical presentations. Despite its specificity limitations, technetium-99m pertechnetate scintigraphy is optimal for evaluating patients with gastrointestinal bleeding, whereas ultrasound demonstrates poor sensitivity. These findings support the adoption of tailored diagnostic strategies and advocate for universal resection in children with symptomatic MD.